Llengua i societat en la medicina tradicional i popular dels segles XVIII i XIX - Martí Mestre, Joaquim (Caplletra. Revista Internacional de Filologia, 2001)
This text constitutes a study and critical edition of a Valencian prescription manuscript, from the beginning of the XIX century, which has remained practically unknown up to the present day. It juxtaposes early instances of the language in this genre with the presence of the traditional forms of the names of diseases or medicines in Valencian popular literature of the XVIII and XIX centuries.